2023
DOI: 10.21203/rs.3.rs-2688073/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Recurrence after Keloid Surgery with Electron Radiotherapy

Chunlei Liu

Abstract: Aim to investigate the local control effect of postoperative electron radiotherapy for keloid and new recurrence risk factors. We collected the clinical data of 82 patients with 129keloids from January 2015 to October 2019. There were 23 males (28%) and 59 females (72%). Median age was 32 years (18-67 years). There were 26 recurrences, and the 1-year, 3-year and 5-year local control rates were 93%, 81% and 73%, respectively. Univariate analysis showed that age (p=0.025), hypertension (p=0.035), scar shape (p&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, one study investigating factors influencing the recurrence rate after keloid surgery reported that age did not emerge as an independent risk factor. 61 Therefore, further research is essential to clarify age's impact on keloid activity. Additionally, differences in sampling procedures could have affected healing of the biopsy site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study investigating factors influencing the recurrence rate after keloid surgery reported that age did not emerge as an independent risk factor. 61 Therefore, further research is essential to clarify age's impact on keloid activity. Additionally, differences in sampling procedures could have affected healing of the biopsy site.…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting our results, considering three patients in their 50s to 60s, underscores the need for nuanced age consideration. However, one study investigating factors influencing the recurrence rate after keloid surgery reported that age did not emerge as an independent risk factor 61 . Therefore, further research is essential to clarify age's impact on keloid activity.…”
Section: Discussionmentioning
confidence: 99%